2021
DOI: 10.1080/19490976.2020.1870402
|View full text |Cite
|
Sign up to set email alerts
|

Association between antibiotics and gut microbiome dysbiosis in children: systematic review and meta-analysis

Abstract: Antibiotics in childhood have been linked with diseases including asthma, juvenile arthritis, type 1 diabetes, Crohn's disease and mental illness. The underlying mechanisms are thought related to dysbiosis of the gut microbiome. We conducted a systematic review of the association between antibiotics and disruption of the pediatric gut microbiome. Searches used MEDLINE, EMBASE and Web of Science. Eligible studies: association between antibiotics and gut microbiome dysbiosis; children 0-18 years; molecular techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
105
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(111 citation statements)
references
References 56 publications
(132 reference statements)
5
105
1
Order By: Relevance
“…Antibioticexposed mice were colonized by two compositionally and functionally distinct low-diversity microbiota (which we termed PAM I and PAM II mice) despite the fact that these were littermates exposed to the same antibiotics. The effects of antibiotic exposure we observed are consistent with the effects reported previously by us and others in mice (Lynn et al, 2018;Ng et al, 2019) and humans (Bokulich et al, 2016;McDonnell et al, 2021;Dethlefsen and Relman, 2011;Hildebrand et al, 2019;Palleja et al, 2018). The importance of different patterns of recolonization following antibiotic exposure on immunity and metabolism in later life are currently poorly understood.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Antibioticexposed mice were colonized by two compositionally and functionally distinct low-diversity microbiota (which we termed PAM I and PAM II mice) despite the fact that these were littermates exposed to the same antibiotics. The effects of antibiotic exposure we observed are consistent with the effects reported previously by us and others in mice (Lynn et al, 2018;Ng et al, 2019) and humans (Bokulich et al, 2016;McDonnell et al, 2021;Dethlefsen and Relman, 2011;Hildebrand et al, 2019;Palleja et al, 2018). The importance of different patterns of recolonization following antibiotic exposure on immunity and metabolism in later life are currently poorly understood.…”
Section: Discussionsupporting
confidence: 91%
“…These pathways included a range of bacterial metabolic pathways, including several involved in SCFA fermentation . The effects of antibiotic exposure we observed, including a significant loss of diversity, blooms of enterobacteria and other pathobionts, and inter-individual/cage variation in the response of the gut microbiota to antibiotics, are consistent with the effects reported previously by us and others in mice (Lynn et al, 2018;Ng et al, 2019) and humans (Bokulich et al, 2016;McDonnell et al, 2021;Dethlefsen and Relman, 2011;Hildebrand et al, 2019;Palleja et al, 2018). We hypothesized that different low-diversity microbiota community types that colonize the gut following antibiotic exposure would differentially affect immunity and metabolism in later life, potentially influencing overall lifespan.…”
Section: Different Low-diversity Microbiota Community Types Colonize the Gut Following Antibiotic Exposuresupporting
confidence: 91%
“…Perturbations in the gut microbiota may lead to disturbed microbial homeostasis, a state termed dysbiosis. Antibiotic treatments are among the strongest inducers of gut dysbiosis [ 2 , 3 ]. Antibiotics are routinely administered to treat active infections or for prophylaxis prior to invasive endoscopic or surgical interventions [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found mixed results associating diversity and antibiotic exposure depending on geography, age of the child, type of antibiotic prescribed, and time since antibiotic exposure, but, generally, antibiotic exposures are associated with stable or decreased withinsample diversity 44 . Consistently, we found NHBCS infants had a statistically significantly (pvalue < 0.05) higher alpha diversity than samples in the DIABIMMUNE Study.…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 94%